2014
DOI: 10.1016/j.ijdevneu.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A VEP study in sleeping and awake one‐month‐old infants and its relation with social behavior

Abstract: With the present study we aimed to analyze the relationship between infants' behavior and their visual evoked-potential (VEPs) response. Specifically, we want to verify differences regarding the VEP response in sleeping and awake infants and if an association between VEP components, in both groups, with neurobehavioral outcome could be identified. To do so, thirty-two full-term and healthy infants, approximately 1-month of age, were assessed through a VEP unpatterned flashlight stimuli paradigm, offered in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…However, for the purposes of this study, we selected Orientation and Regulation of State domains. Both domains are assumed to reflect adjusted social‐like characteristics in young infants since orienting (behavioral interactive characteristics) and regulatory abilities are suggested to be basic competences associated with the infant's ability to attend to and modulate their behavior in order to respond adequately to the surrounding environmental interactions (Brazelton & Nugent, ; Calkins, ; Cruz, Crego, Ribeiro, Goncalves, & Sampaio, ; Sprangler et al, ). We used the vagal response as a physiological marker correlated with adjusted social behavior in young infants (higher scores in these NBAS domains) since these two domains are associated with social features displayed by very young infants (Brazelton & Nugent, ; Lester et al, ) and the RSA measure is frequently used as an indicator of social engagement (Porges, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, for the purposes of this study, we selected Orientation and Regulation of State domains. Both domains are assumed to reflect adjusted social‐like characteristics in young infants since orienting (behavioral interactive characteristics) and regulatory abilities are suggested to be basic competences associated with the infant's ability to attend to and modulate their behavior in order to respond adequately to the surrounding environmental interactions (Brazelton & Nugent, ; Calkins, ; Cruz, Crego, Ribeiro, Goncalves, & Sampaio, ; Sprangler et al, ). We used the vagal response as a physiological marker correlated with adjusted social behavior in young infants (higher scores in these NBAS domains) since these two domains are associated with social features displayed by very young infants (Brazelton & Nugent, ; Lester et al, ) and the RSA measure is frequently used as an indicator of social engagement (Porges, ).…”
Section: Methodsmentioning
confidence: 99%
“…Wakefulness is characterized by strong diffuse motor activity, open eyes and irregular breathing and a fourth behavioral state, indeterminate state, gradually disappears with age. Hence, the presence of different electrical activity during QS and AS in the newborn suggests a different brain response to visual stimulation during QS and AS; however, even though VEPs have often been studied in newborns to assess neurodevelopment and identify abnormal development of the visual pathways (Cruz et al, 2015; McGlone et al, 2013; Kato and Watanabe, 2006), not all studies in newborns have taken into account the behavioral state of infants when recording VEPs, thus the effect of sleep states on neonatal VEPs remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in newborns have carried out VEPs recording only during wakefulness (Roy et al, 2004; Kraemer et al, 1999), some others differentiated between wakefulness and sleep and found significant differences in amplitude and latencies between the two states but did not analyze AS and QS separately (Cruz et al, 2015; Benavente et al, 2005; Tsuneishi et al, 1995). Those studies separating VEPs in QS and AS, based only on behavioral observation found no differences between the two states (Shepherd et al, 2000; Mercuri et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonates process information while asleep. For example, they actively respond to auditory and visual stimuli while asleep (Cheour et al, 2002; Cruz, Crego, Ribeiro, Goncalves, & Sampaio, 2015; deRegnier, Nelson, Thomas, Wewerka, & Georgieff, 2000; Kotilahti et al, 2010; Sambeth, Ruohio, Alku, Fellman, & Huotilainen, 2008). Event related potential (ERP) studies show a differential response to mother’s voice versus a stranger’s voice (deRegnier et al, 2000) and a mis-match response to fearful versus angry voices (Zhang et al, 2014).…”
Section: | Introductionmentioning
confidence: 99%